Sustainable Marketing and Changes in Consumer Preferences in the Era of Environmental Awareness - Vivi Ristanti (PT. Anagata Sembagi Education, 2025)
The growing global awareness of environmental degradation has significantly reshaped market dynamics and consumer expectations, positioning sustainability as a strategic imperative for contemporary businesses. This study investigates how sustainable marketing influences consumer preference shifts in the context of rising environmental consciousness and examines mechanisms for reducing the persistent attitude–behavior gap in green consumption. A systematic literature review was conducted using PRISMA guidelines, analyzing peer-reviewed journal articles published between 2020 and 2025 and indexed in Scopus and related academic databases. The findings demonstrate that environmental awareness, pro-environmental attitudes, ethical values, and sustainable lifestyles strongly affect consumers’ purchase intentions and preferences toward green products, particularly among younger, educated, and higher-income segments. However, economic constraints, price sensitivity, information asymmetry, and skepticism toward greenwashing remain major barriers preventing consistent sustainable purchasing behavior. The discussion reveals that integrated sustainable marketing strategies incorporating green marketing mix elements, transparent communication, credible eco-labeling, digital engagement, and continuous environmental education play a decisive role in converting environmental concern into actual purchasing behavior. In conclusion, sustainable marketing holds substantial potential to reshape consumer preferences and accelerate the transition toward sustainable consumption, provided that strategic alignment among education, affordability, institutional trust, and social influence is achieved.